Clinical diagnostic criteria of benign adult familial myoclonus epilepsy type 1 are highly concordant with genetic testing. Issue 3 (6th February 2023) - Ishibashi, Haruka; Kobayashi, Katsuya; Tojima, Maya; Neshige, Shuichiro; Hitomi, Takefumi; Ishiura, Hiroyuki; Tsuji, Shoji; Maruyama, Hirofumi; Takahashi, Ryosuke; Ikeda, Akio
Abstract: Background: The clinical diagnostic criteria for benign adult familial myoclonus epilepsy (BAFME) originally included (1) cortical tremor and infrequent generalized seizures, (2) autosomal dominant inheritance, (3) lack of cognitive decline and other neurological symptoms, (4) electrophysiological findings of cortical reflex myoclonus, and (5) lack of clear clinical progression (BAFME criteria‐1). It was revised such that (1) included partial seizures, and (3) and (5) may develop among middle‐aged patients (Revised criteria‐2). The Japanese Ministry of Health, Labor and Welfare proposed their criteria, which included the EEG and MRI findings (MHLW criteria‐3). Recently, high‐frequency oscillations, superimposed on the giant somatosensory evoked potential P25 component (P25‐HFOs), have been found useful as a biomarker for BAFME diagnosis. Aim: We examined the genetic diagnosis of BAFME type 1 and its consistency with the three diagnostic criteria and P25‐HFOs. Methods: Twenty‐four Japanese patients, who underwent BAFME genetic testing, were rated using three independent diagnostic criteria and P25‐HFOs. Results: Twenty‐one patients were genetically diagnosed with BAFME type 1. Nineteen patients fulfilled BAFME‐1 (sensitivity 90%), and 21 fulfilled Revised‐2 and MHLW criteria‐3 (sensitivity 100%). We could evaluate P25‐HFOs in 19 of the 21 gene‐positive patients, and 17 of the 19 patients showed P25‐HFOs. Three patients with negative genetic testing did not meet any of the criteria and had no P25‐HFOs. Conclusions: The three available clinical diagnostic criteria for BAFME were highly concordant with the positive result for genetic testing.